Young Europeans – A Tourism Opportunity for the Capital City - Ana-Maria Nica (Cactus, 2019)
Tourism has experienced a spectacular boom in recent years, with over one billion people spending at least one vacation in a country other than home. This is mainly due to the increase of the standard of living in more and more countries, the increase of the duration of the leave and of the leisure time in general, but also the decreasing tariffs of the tourist services and the easier access to the tourist resources. With the development of tourism, a form of it has become widespread, namely urban tourism. This is mainly due to people's growing interest in culture and knowledge of new places. The cities also offer a full range of attractions and leisure opportunities. Cities and tourism in these are very well promoted by the ministries and tourist offices in Europe, while Romania does not promote among the potential tourists the urban destinations of our country. The present article is aimed at filling the gap related to the expectations of foreign tourists regarding Romania. The study is focused on young people, aged 25-35 years, active on the labor market, and interested in short, intense, city-break type of travelling. The results of the research are presented in the second part of the article.